O6.5. JUMPING TO CONCLUSIONS ABOUT DECISION NOISE? A COMPUTATIONAL ANALYSIS OF THE RELATIONSHIP BETWEEN BELIEF UPDATING AND PSYCHOTIC SYMPTOMS IN A LARGE UK BIRTH COHORT. (18th May 2020) - Croft, Jazz; Heron, Jon; Teufel, Christoph; Adams, Rick; David, Anthony; Fletcher, Paul; Linden, David; Zammit, Stanley
Abstract: Background: A number of studies show that people with psychotic disorders have abnormal belief-updating processes. In a commonly-used decision-making task, the beads task, participants infer which of two jars, each with a different ratio of coloured beads, a presented bead is drawn from, with an option to request further beads before reaching a decision. Previous studies suggest that people with psychotic symptoms request fewer beads (draws to decision; DTD) indicative of a 'Jumping to conclusion' (JTC) bias. In a modified version of this task, participants estimate the probability that beads have been drawn from one of the two jars on a sliding scale over a sequence of beads and are also told that the jar the beads are drawn from may switch. In this task, people with psychotic symptoms revise their estimations disproportionately in response to a change in colour of beads in a sequence (overadjustment bias). It is not clear what specific belief-updating processes drive these biases, how they arise, or if their association with psychotic symptoms is independent of confounding. We examined whether abnormal belief-updating processes are associated with psychotic experiences in a large, population-based sample, and whether they mediate the association between trauma and psychotic symptoms. Methods: We used data from the Avon Longitudinal Study of Parents and Children birth cohort (n=2, 879). Past-year frequent or distressing psychotic experiences (PEs) were assessed using the semi-structured PLIKS interview at age 24. Performance on the DTD and probability estimation tasks at age 24 were assessed using behavioural indices and computational modelling parameters (using 'costed Bayesian' and Hidden Markov Models respectively). Logistic regression was used to examine the association between belief-updating parameters (DTD task: cost of sampling, decision noise; Probability estimation task: adjustment rate, inference length, decision confidence, prior expectation of reversal, decision noise) and PEs. Estimates were adjusted for confounders (genetic risk for schizophrenia, socio-economic status, cognitive function). Mediation analysis tested abnormal belief-updating processes as a mediator between exposure to trauma (assessed ages 0–17 years) and age-24 PEs. Results: In the DTD task, increased decision noise was associated with PEs (adjusted OR=1.89, 95% CI: 1.14, 3.13, p=0.014). There was little evidence of an association between the JTC bias and PEs (OR= 1.13; 95% CI: 0.45, 2.82). For the probability estimation task, there was an association between a higher prior expectation that the jars that will switch during the sequence (expectation of reversal) and PEs (adjusted OR = 2.28; 95% CI 1.39, 3.74, p=0.001). Our findings were minimally attenuated by confounding (<10%). Exposure to trauma was also associated with greater decision noise in the DTD task, but there was little evidence that this abnormal belief-updating parameter mediated the relationship between trauma and PEs (<1% mediated). Discussion: Our results suggest that abnormal belief-updating processes (increased decision noise; greater prior expectation of reversal) are associated with PEs, and that this is not explained by general cognitive ability, shared genetic risk, or social background. Previous observations of association between the JTC bias and psychosis may be due to sub-optimal performance rather than a bias for making a decision on less evidence. The results also suggest that an increased expectation of change is associated with the early stages of psychosis symptom development. Our mediation result does not support the hypothesis that the belief-updating processes examined here lie on the causal pathway between trauma exposure and PEs.